PROGRESS IN ORGAN DONATION AND TRANSPLANTATION IN RUSSIAN FEDERATION IN 2006–2010. 3RD REPORT OF NATIONAL REGISTRY - S. V. Gautier; Y. G. Moysyuk; S. M. Khomyakov; O. S. Ibragimova (Вестник трансплантологии и искусственных органов)
The article presents the third report of the Registry of Russian transplant society, taking into account donor and transplant activity in the Russian Federation in 2006–2010. Data analysis proves clear positive trends during the last 5 years. The further progress is possible through the creation and modernization of regional donor infra- structures whose activities should be aimed at increasing of the number of donor hospitals and its rational use by expansion of brain death verification and performance of multiorgan procurement.